All you need for a beach - Schertle, Alice (Silver Whistle/Harcourt, 2004)
Rhyming text describes items essential for fun at the beach, from the first grain of sand, to a beach umbrella, to a bucket and shovel, to the waves rolling in to tickle your toes.